Políticas e práticas de educação inclusiva para pessoas com deficiência visual: o caso da Escola de Música de Brasília - Vieira, Paulo Sérgio José (2018)
This main goal of this study is to analyze the public policies and practices of inclusive education for students with visual impairment at Escola de Música de Brasília, Brazil. For this purpose, a qualitative and exploratory survey was conducted using document analysis; semi-structured interviews and direct observation in regular classes and in the Resource Room, constituting a case-study. Five students with visual impairment, five teachers of regular classes and one teacher of the Resource Room took part in this study. For the theoretical frame the ideas of Glat (1995), Mantoan (2003, 2006), Prieto (2006, 2009), Bonilha (2006), Mattos and Pinheiro (2007), Garcia and Michels (2011), Bardin (2011), Baptista (2011), Glat and Pletsch (2012), Salomão (2013), and also Vasconcelos and Síveres (2018) were used. Several international documents were consulted, such as The Universal Declaration of Human Rights (1948), The Salamanca Statement (1994) and The Inter-American Convention on the Elimination of All Forms of Discrimination against Persons with Disabilities (1999). National legislation, including the Brazilian Constitution of 1988, was also consulted, in addition to local legislation. The data generated was submitted to content analysis. On the theme of public policies, the main characteristic is that according to the documents, all the spaces of educational services are inclusive. As far as the success of the practice of inclusion is concerned, the results expose, as a positive aspect of SES (Special Education Services) the support the students receive in the Resource Rooms, which promote aspects of development that are essential to enable educational inclusion. On the other hand, the drawbacks this study has identified include the lack of continuing educational courses, the lack of teaching resources, as well as the lack of appropriate assets and assistive technology to promote the educational inclusion process in the school that was surveyed. The demands of the entrance examination force the visually impaired students to compete in the same terms with all the other students. The main strategies observed in the teaching practices were the partnership between the Resource Class teacher and the teachers of regular classes to promote the learning process and the creation of a pleasant and motivating environment for the visually impaired students in the Specific Resource Room. The study arrives at the conclusion that there are weaknesses and difficulties in the process of including visually impaired students. Thus, the need to strengthen the entire structures of SES should be considered throughout the school context involved in the educational inclusion process.